Caminhos e obstáculos para o acesso à justiça: 'o caso do Programa Mediação de Conflitos em Minas Gerais' - Leandro, Ariane Gontijo Lopes (2012)
Our goal in this work is to demonstrate some paths and obstacles related to access to justice for the population served by the Conflict Mediation Program of the State of Minas Gerais. The issue of access to justice has been the focus of extensive studies on the democratization of rights in Brazil. Researchers from the social sciences and humans have dedicated their productions to the goal of understanding the phenomenon of rights and its form of organization-implementation in the country. The various initiatives of decentralization of rights – given the need to expand them, especially for low-income population – had causing extensive reflections on the political system and justice in Brazil, with special attention to dilemmas found in historical and cultural characteristics the country, allowing them apart and bring them closer to other national contexts. The calling up of the democratic principle extends and increases the institutionalization of law in social life, covering spaces that are not yet expressed that he did so, legalizing mainly the sphere of private life. This set of elements is essential to this work, since they present the development and implementation of the Conflict Mediation Program. We seek to present the creation of this program since its inception, as action research project from the conception of legal pluralism and the 'law found in the street.' His formulation, carried out by means of reflections arising from a group of professors from the field of Law from Federal University of Minas Gerais, during the 90's created an extension program at the same university – called 'Pólos for Citizenship' – led us to understanding of your route and paths taken. We discuss the main challenges in implementing methods of informal justice mechanisms and conflict resolution. This is a qualitative study in which some socioeconomic data were incorporated for analytical purposes. We emphasize, above all, the course of this experience by its creators, we present some results related to the data already produced by this practice and who are the operators of this experience today – the mediators, and we seek to identify what are the perceptions of those who were served by this program – their speeches and personal stories – and what are the paths indicated by this segment of society for that 'access to justice' becomes possible to accomplish.